“The Other” in Serbian and Croatian Literature after the Disintegration of Yugoslavia: the Example of Slobodan Selenić - Cidilko, Vesna (Zeitschrift für Balkanologie, 2023)
The portrayal of the other ethnic group, but also the portrayal of one’s own national community, from which one originates or to which one feels one belongs, has been included in public statements of all kinds in Yugoslavia after 1945, with varying intensity and changing intentions. The image of the “other” and also of one’s own ethnic group that found its way into literature depended on the political climate from the very beginning. Depending on the state’s precepts and the prevailing situation, the view of the “other” was either hindered, tolerated or encouraged. This was also true, even if the situation was different from that in the countries of the Eastern Bloc, for other explicit political topics. After the disintegration of the country and the wars in the nineties of the last century, the time seemed to have come for some Serbian and Croatian writers to be able now to write about the other nation in an exclusively negative way. However, such political engagement and the role of writers were immediately perceived polemically, both by the Croatian and Serbian public – even if they were evaluated differently by official cultural policies of both states during the last decade of the 20th century. The literature testifies to different developments in the representation of the most recent period in the common history of the Serbs and the Croats, closely linked to the likewise differently handled portrayal of the two ethnic groups after the disintegration of the common state. It is a development that has yet to be grasped in its entirety. A first step in this direction is the “sifting” of the literary work of individual authors in order to be able to put together an overall picture from these “individual parts”. This is attempted in the present text using the example of the novel works of Slobodan Selenić.